1974
DOI: 10.1172/jci107691
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin in Clinically Uninvolved Skin in Systemic Lupus Erythematosus ASSOCIATION WITH RENAL DISEASE

Abstract: [LBT]). In patients with low serum complement levels, 91% had a positive LBT), as compared with 15% in those with normal complement levels. The LBT was positive in 70% of patients with clinical and laboratory evidence of renal disease, but in only 31% of patients without renal disease. 81% of patients with the more severe histologic forms of lupus nephritis, i.e., proliferative glomerulonephritis and membranous glomerulonephritis, had positive tests, whereas only 23% with mesangial glomerulitis or normal histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

1975
1975
1982
1982

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(32 citation statements)
references
References 24 publications
3
29
0
Order By: Relevance
“…Others have correlated a positive lupus band test with disease activity (21,22,24) and we now document an association between deposition of a specific protein and disease activity. Our data revealed that IgA was absent in all nonlesional skin from patients with no evidence of clinical disease activity, while it was present in 7 of 23 with active disease.…”
Section: Methodssupporting
confidence: 72%
See 2 more Smart Citations
“…Others have correlated a positive lupus band test with disease activity (21,22,24) and we now document an association between deposition of a specific protein and disease activity. Our data revealed that IgA was absent in all nonlesional skin from patients with no evidence of clinical disease activity, while it was present in 7 of 23 with active disease.…”
Section: Methodssupporting
confidence: 72%
“…Similar deposits have been described in the dermalepidermal junction (DEJ) of normal and lesional skin of SLE patients (18)(19)(20)(21). Several authors have correlated the presence in normal skin of immunoglobulins and complement (the "lupus band test") with lupus nephritis (21,22). Others have found no such correlation (23,24).…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…3-mm punch biopsies were obtained from the light protected uninvolved skin of the medial surface of the volar forearm. Processing of the tissue and immunofluorescent tests were carried out as previously described (11).…”
Section: Methodsmentioning
confidence: 99%
“…However, some other researchers did not reach this conclusion (8)(9)(10)(11)(12). We and some investigators also noted a correlation between serologic evidence of disease activity and the dermal-epidermal junction deposits (1)(2)(3)(4)(5)6,8,13), but this was not found by others (9,11,12). The relationship of such deposits to the presence of renal disease also has Seen disputed To clarify the relationship between clinical disease activity, renal disease, and serologic abnormalities, we studied a group of patients with systemic lupus erythematosus at 2 points in the course of their disease.…”
Section: Studies Of Repeat Skin Biopsies Of Nonlesional Skin In Patiementioning
confidence: 45%